Boats! - Reasoner, Charles 1949- (Guangdong : Power Printing, 2011)
The Big Busy Machines: Boats! board book provides the perfect way to introduce reading in your home. Children will learn all about transportation as cute and colorful illustrations bring boats to life. This book engages early learners by using short, simple language.
D
b
D
Keywords: Juvenile literature